ICT and social and civic competence (Journal of Parents and Teachers, 2014)
In the teacher’s role it has always been implicit the fact of educating citizens who actively participate in society life and at the same time making them develop a sense of critic. Now, in every educative stage, this is evaluated. This is why, to develop this competency suitably, work in class should give: personal relationships, cooperative work, democratic participation, values practice, understanding and involment.
Keywords: new technologies; TIC; basic competencies; social and citizen competency